Konfigurasi Layout Area Kerja Berdasarkan Preferensi Pengguna (Studi Kasus : Area Kerja Dosen Desain Interior, Universitas Telkom) - Palupi, Fajarsani Retno (Program Studi Desain Interior Unikom, 2024)
The typical workday lasts between eight and nine hours, with employees spending a significant portion of their time at the office. This makes the office a second home for many, where they spend their productive time. Therefore, it is crucial to ensure that the office space is well-organized and comfortable, as it plays a vital role in supporting the physical comfort of its users. The layout of the office space and the furniture arrangement must be carefully considered to accommodate the various activities that take place within it. This arrangement can be analysed in several ways in order to obtain the most efficient results according to the activities of office work area users. This research was conducted in the workspace of interior design lecturers at Universitas Telkom, with a kasus studi approach, using data collection techniques in the form of direct observation of ongoing activities and data collection of types of cubicle layout arrangements in the work area. The research focuses on three key areas: the arrangement of the work area, the circulation of the work area, and the primary activities that occur in the workspace. The study revealed that each user organises their work area according to their personal needs and comfort, in accordance with the activities that take place in their respective workspaces. Keywords: Layout, working area, cubicle type, efficiency